2012
DOI: 10.1016/j.aorn.2012.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Perfecting Patient Flow in the Surgical Setting

Abstract: Reduced surgical efficiency and productivity, delayed patient discharges, and prolonged use of hospital resources are the results of an OR that is unable to move patients to the postanesthesia care unit or other patient units. A primary reason for perioperative patient flow delay is the lack of hospital beds to accommodate surgical patients, which consequently causes backups of patients currently in the surgical suite. In one facility, implementing Six Sigma methodology helped to improve OR patient flow by ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…[1][2][3][4] For perforator flap breast reconstruction, intraoperative pathways can lead to improvements in operative time, cost, quality measures, and staff satisfaction, but such success is dependent on developing a team-based model of health care delivery, which must focus on interdisciplinary communication, enhanced efficiency through standardization of practice, and eliminating unnecessary steps, especially for lengthy procedures.…”
mentioning
confidence: 99%
“…[1][2][3][4] For perforator flap breast reconstruction, intraoperative pathways can lead to improvements in operative time, cost, quality measures, and staff satisfaction, but such success is dependent on developing a team-based model of health care delivery, which must focus on interdisciplinary communication, enhanced efficiency through standardization of practice, and eliminating unnecessary steps, especially for lengthy procedures.…”
mentioning
confidence: 99%
“…In the surgical setting, a set of integrated recommendations (i.e. anticipated discharge date, notifying family members of the discharge time and defining standard discharge responsibilities for key individuals) involving the Operating Room, the Intensive Care Unit and Surgical Care Units improved the admission and discharge process (Williams et al , 2011; Amato-Vealey et al , 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The effectiveness of multi-professional teams to improve patient flow and clinical outcomes has been tested by several studies (Alikhan et al , 2009; Amato-Vealey et al , 2012; Borenstein et al , 2016; Chadaga et al , 2012; Dickson et al , 2009; Elliot et al , 2015; Evans et al , 2011; Healy-Rodriguez et al , 2014; Jweinat et al , 2013; Lovett et al , 2014; Muntlin Athlin et al , 2013; Odom et al , 2018; Ortiga et al , 2012; Sánchez et al , 2018; Yancer et al , 2006). Some examples include the development of a Hospital Medicine ED Team consisting of hospital medicine physicians, ED physicians, social workers and nurses (Chadaga et al , 2012); the development of a multi-professional team responsible for the whole care process for a group of patients (Muntlin Athlin et al , 2013); the incorporating of one logistic manager and two registered nurses in a logistics management program (Healy-Rodriguez et al , 2014).…”
Section: Resultsmentioning
confidence: 99%
“…According to several authors, a coordinated multidisciplinary process redesign involving anesthesiologists, surgeons, and nurses are key to improving OR productivity, lowering OR turnover time, and anesthesia-related time. [14][15][16][17][18][19] Some authors have demonstrated that introducing these manufacturing industry tools to surgical practice are objective methods for detecting variances and identifying areas for implementing changes. 13,14 In surgery, LM focuses on reducing waste in a process, and SS reduces process variation through the application of statistical methods.…”
Section: Discussionmentioning
confidence: 99%